THE INFLUENCE OF WORD OF MOUTH AND PRICE PERSPECTIVE ON CUSTOMER PURCHASE INTENTION. A CASE STUDY OF “INDRIVE” USERS OF FACULTY OF ECONOMICS AND BUSINESS STUDENTS - Sharon Lontoh; James Massie; Merinda Pandowo (Universitas Sam Ratulangi, 2023)
This study aims to determine the influence of word of mouth and price perspective on customer purchase intention. A case study of “InDrive” users of Faculty of Economics and Business students both simultaneously and partially. This study uses a quantitative method with a sample of 100 respondents and uses purposive sampling technique. Data collection using a questionnaire. Statistical data analysis using multiple linear regression analysis, hypothesis testing using the F and T tests. The results showed that, simultaneously the Word Of Mouth and Price perspective positively had influence on Customer Purchase Intention of “InDrive” users of Faculty of Economics and Business students. Partially, the Word Of Mouth and Price Perspective have a positive influence on Customer Purchase Intention of “InDrive” users of Faculty of Economics and Business students Keywords: word of mouth, price perspective, purchase intention